LITHOLOGY UNITS PENGKOL AREA AND SURROUNDING, GUNUNG KIDUL DISTRICT, YOGYAKARTA PROVINCE. - Gani, Reza Mohammad Ganjar; Firmansyah, Yusi; Nurdeani, Rifky (Journal of Geological Sciences and Applied Geology, 2021)
The research area is located sub-district Nglipar,District of Gunnung Kidul,Yogyakarta Province. Accessibility to the research location by train Bandung - Yogyakarta, followed by a minibus to Nglipar District Gunung Kidul. Purpose Of this Research is to understanding geological conditions of the research area reviewed from litohologic units and  its stratigraphic order. The lithostratigraphy of the research area is divided into 3 lithologic units, Breccia Unit, Sandstone Unit and Limestone Unit. namely the naming of the rock units based on observable physical characteristics, including rock type, uniformity lithology symptoms and their stratigraphic position. Geological history at the location of this study is the eruption of Mount Ngalanggran and deposited volcanic breccia units. Early Miocene deposited units sandstone. At that time there was a decrease in sea level which caused the diagenesis of the sedimentary material into limestone material. On Middle Miocene limestone deposited. Keyword: Lithologic units, stratigraphic order, Gunung Kidul District.